2015
DOI: 10.5152/akd.2014.5656
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tirofiban infusion on clinical and angiographic outcomes of patients with STEMI undergoing primary PCI

Abstract: Objective:The present study was designed to determine the effects of tirofiban (Tiro) infusion on angiographic measures, ST-segment resolution, and clinical outcomes in patients with STEMI undergoing PCI. Glycoprotein (GP) IIb/IIIa inhibitors are beneficial in ST-segment elevation myocardial infarction (STEMI) patients undergoing percutaneous coronary intervention (PCI), while the most effective timing of administration is still under investigation.Methods:A total of 1242 patients (83.0% males, mean (standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…3 Moreover also in large real word STEMI population tirofiban administration prior to primary PCI showed significant improvement in myocardial reperfusion, ST-segment resolution and in-hospital mortality rate. 19 Interestingly, in our analysis, early tirofiban administration effect on NT-proBNP level post-PCI was independent from baseline NT-proBNP level. Indeed, although baseline NT-proBNP level was related to post-PCI level and baseline NT-proBNP has been correlated to microvascular obstruction after PCI, 20 it has been shown that patients with higher baseline level of NT-proBNP may derive particular clinical benefit from early GPIs treatment.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…3 Moreover also in large real word STEMI population tirofiban administration prior to primary PCI showed significant improvement in myocardial reperfusion, ST-segment resolution and in-hospital mortality rate. 19 Interestingly, in our analysis, early tirofiban administration effect on NT-proBNP level post-PCI was independent from baseline NT-proBNP level. Indeed, although baseline NT-proBNP level was related to post-PCI level and baseline NT-proBNP has been correlated to microvascular obstruction after PCI, 20 it has been shown that patients with higher baseline level of NT-proBNP may derive particular clinical benefit from early GPIs treatment.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover also in large real word STEMI population tirofiban administration prior to primary PCI showed significant improvement in myocardial reperfusion, ST‐segment resolution and in‐hospital mortality rate …”
Section: Discussionmentioning
confidence: 91%
“…The substantial finding of our study is that, administration of double high-dose intracoronary bolus tirofiban in STEMI patients undergoing primary PCI, in addition to aspirin, heparin, and high-dose clopidogrel, wasassociated with lower 30-day TVR rates without leading to a significant increase in minor or major bleeding.However, it did not significantly affect MACE and all-cause mortality rates. Unlike the trials involved low-dose bolus regimens [6][7][8][9], studies involving the high-dose bolus regimen of tirofiban support its efficacy and safety in patients with STEMI undergoing primary PCI [10][11][12]. To the best of our knowledge, this is the first study in the literature comparing the efficacy and safety of the single highdose versus double high-dose intracoronary bolus tirofiban in patients undergoing primary PCI.…”
Section: Discussionmentioning
confidence: 93%
“…Tirofiban is a highly selective anda short-acting platelet glycoprotein (GP) IIb/IIIa receptor inhibitor,which inhibits platelet aggregation by blocking the combination of fibrinogen and GP IIb/IIIa and consequently prevents myocardial ischemia caused by coronary thrombosis [4,5]. Regarding tirofiban dosage, unlike the trials of low-dose bolus regimens [6][7][8][9], recent studies involving the high-dose bolus regimen support its efficacy in patients with STEMI undergoing primary PCI [10][11][12]. These results may translate to clinical benefit while not significantly increasing bleeding complications.Not only the optimal doses but also the ideal route of administration of GP IIb/IIIa receptor inhibitors has also been actively investigated [13,14].…”
mentioning
confidence: 99%
“…Lately, several studies [1][2][3] showed that GPIIb/IIIa inhibitors improve outcome in ACS patients with or without any coronary intervention. However, various studies [4][5][6][7] showed that the adjunctive treatment with tirofiban does not confer any clinical benefit, as compared with placebo or other antiplatelet drugs, such as abciximab and ticagrelor [8]. Thus, controversy still exists in the clinical efficacy of tirofiban on ACS.…”
Section: Discussionmentioning
confidence: 99%